Rinus van der Lubbe, 1909-1934 - Schouten, Martin, 1938- (Amsterdam : Bezige Bij, 1986)
Biografie van de Leidse politieke activist, die in 1933 brand stichtte in het gebouw van de Rijksdag in Berlijn
Keywords: Lubbe, van der, Marinus, -- 1909-1934.